Does remission in rheumatoid arthritis bring kinesiophobia, quality of life, fatigue, and physical activity closer to normal? - Aysun Özlü; Merve Akdeniz Leblebicier (Archives of Rheumatology, 2022)
Objectives: This study aimed to compare kinesiophobia, fatigue, physical activity, and quality of life (QoL) between the patients with rheumatoid arthritis (RA) in remission and a healthy population. Patients and methods: The prospective controlled study included 45 female patients (mean age: 54.22±8.2 year; range, 37 to 67 year) with a diagnosis of RA determined to be in remission according to the Disease Activity Score in 28 Joints (DAS28) being ≤2.6 between January 2022 and February 2022. As a control group, 45 female healthy volunteers (mean age: 52.2±8.2 year; range, 34 to 70 year) of similar age were evaluated. The QoL, disease activity, pain, kinesiophobia, fatigue severity, and physical activity were assessed using the Health Assessment Questionnaire, DAS28, Visual Analog Scale, Tampa Scale of Kinesiophobia, Fatigue Severity Scale, and International Physical Activity Questionnaire, respectively. Results: There was no significant difference between the groups in demographic data. A statistically significant difference was found between the groups in terms of pain, C-reactive protein level, fatigue, kinesiophobia, QoL, and total, high, and moderate physical activity scores (p<0.001). Among the RA patients in remission, there was a significant correlation between kinesiophobia and moderate physical activity and QoL, as well as between fatigue and high physical activity (p<0.05). Conclusion: Patient education and multidisciplinary approach strategies should be developed to increase the QoL and physical activity and reduce kinesiophobia in RA patients in remission since there may be a decrease in physical activity due to kinesiophobia, fatigue, and fear of movement in this patient group compared to the healthy population, impairing their QoL.